Shared Decision-Making, Sphincter Preservation, and Rectal Cancer Treatment: Identifying and Executing What Matters Most to Patients - Ivatury, Srinivas Joga; Suwanabol, Pasithorn A.; Roo, Ana C. De (Clinics in Colon and Rectal Surgery, 2023)
Rectal cancer treatment often encompasses multiple steps and options, with benefits and risks that vary based on the individual. Additionally, patients facing rectal cancer often have preferences regarding overall quality of life, which includes bowel function, sphincter preservation, and ostomies. This article reviews these data in the context of shared decision-making approaches in an effort to better inform patients deliberating treatment options for rectal cancer.
Keywords: shared decision making; rectal cancer; sphincter-preservation; ostomy